2016
DOI: 10.3892/ijmm.2016.2753
|View full text |Cite
|
Sign up to set email alerts
|

Expression of glycine receptors and gephyrin in rat medial vestibular nuclei and flocculi following unilateral labyrinthectomy

Abstract: The medial vestibular nucleus (MVN) and the cerebellar flocculus have been known to be the key areas involved in vestibular compensation (VC) following unilateral labyrinthectomy (UL). In this study, we examined the role of gephyrin and glycine receptor (GlyR) in VC using Sprague-Dawley rats, in an aim to gain deeper insight into the mechanisms responsible for VC. The expression of the α1 and β subunits of GlyR and gephyrin was immunohistochemically localized in rat MVN and flocculi. The mRNA and protein expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…UL 13 , 14 was performed on the right side of male SD rats aged 8–10 weeks under anesthesia. The operator made an incision, opened the tympanic bulla wall, removed the tympanic bulla, malleus, and incus, and destroyed the vestibule with absolute alcohol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…UL 13 , 14 was performed on the right side of male SD rats aged 8–10 weeks under anesthesia. The operator made an incision, opened the tympanic bulla wall, removed the tympanic bulla, malleus, and incus, and destroyed the vestibule with absolute alcohol.…”
Section: Methodsmentioning
confidence: 99%
“…Blinded assessors scored the static symptoms of vestibular imbalance, 8 , 13 , 14 , 16 , 17 including spontaneous nystagmus, head tilt, postural asymmetry, and tall‐hanging test, presented in behavioral tests. Spontaneous nystagmus was recorded by a video eye‐tracking system and scored on a scale of 6~10 points in terms of bpm.…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis indicated that the optimal intervention time might be less than 6 weeks and multisensory exercises beyond 6 weeks are not necessary. And animal studies showed the time taken for vestibular compensation was no more than 7 days [70,71] . The intervention time should suffice to modulate central nervous plasticity.…”
Section: Synthesized Findingsmentioning
confidence: 99%
“…Despite their small number, interneurons are essential for the homeostasis of neural circuits in the brain, where they attach to specific excitatory inputs and provide feedforward and feedback inhibition to pyramidal neurons, maintaining homeostasis of neural activity in the brain 21,22 . Gephyrin, an inhibitory postsynaptic protein, is widely distributed in the CA1, CA3, and DG of TLE rats 23 . In addition, the onset of seizures reduced gephyrin expression in the hippocampus and adjacent neocortex 24 .…”
Section: Introductionmentioning
confidence: 99%
“… 21 , 22 Gephyrin, an inhibitory postsynaptic protein, is widely distributed in the CA1, CA3, and DG of TLE rats. 23 In addition, the onset of seizures reduced gephyrin expression in the hippocampus and adjacent neocortex. 24 Furthermore, gephyrin significantly downregulated in the human temporal neocortex in patients with mesial temporal lobe epilepsy (mTLE).…”
Section: Introductionmentioning
confidence: 99%